Well-differentiated “lipoma-like” giant paratesticular liposar-coma: a case report - Dubeux, Victor Teixeira; Campos, Tadeu; Sobel, Jan Michael; Rodrigues, Lucas Shulze; Ferrer, Pedro (Brazilian Journal of Case Reports, 2022)
Few cases of paratesticular liposarcomas have been described in literature and they are considered as rare tumors, especially when they are larger than 10 cm, called giant tumors. We describe the case of a 52-year-old patient diagnosed with a painless mass in the scrotum, initially submitted to magnetic resonance imaging, which revealed a large paratesticular mass. Subsequently, he underwent left radical orchiectomy, which revealed a well-differentiated, “lipoma-like,” “giant” paratesticular liposarcoma. We discussed the workup and current management of this pathology.